2023
DOI: 10.1186/s12889-023-15154-4
|View full text |Cite
|
Sign up to set email alerts
|

Migrant and native women’s perceptions of prenatal care communication quality: the role of host-country language proficiency

Abstract: Background Despite the potentially significant impact of women-prenatal care provider communication quality (WPCQ) on women’s perinatal health, evidence on the determinants of those perceptions is still lacking, particularly among migrant women. Methods We aimed to examine the effect of women’s host-country language proficiency on their perceived WPCQ. We analyzed the data of 1210 migrant and 1400 native women who gave birth at Portuguese public ho… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 39 publications
0
5
0
Order By: Relevance
“…We did not have appropriate data on the healthcare professionals attending childbirth to test this hypothesis. Second, migrant status may affect how healthcare providers perceive patients’ ability to communicate and understand medical information [ 17 , 55 ]. Migrant women might also have low health literacy and/or limited host-country language skills resulting in poorer empowerment and capacity to participate in medical decisions [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We did not have appropriate data on the healthcare professionals attending childbirth to test this hypothesis. Second, migrant status may affect how healthcare providers perceive patients’ ability to communicate and understand medical information [ 17 , 55 ]. Migrant women might also have low health literacy and/or limited host-country language skills resulting in poorer empowerment and capacity to participate in medical decisions [ 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…Migrant women might also have low health literacy and/or limited host-country language skills resulting in poorer empowerment and capacity to participate in medical decisions [ 58 ]. Communication difficulties prevent adequate information and consent [ 17 , 18 ] and could lead to more obstetric interventions, particularly during instrumental delivery, which is a potentially stressful and painful emergency situation. Finally, healthcare professionals’ practices can be influenced by implicit biases, which refer to unconscious negative feelings or stereotypes against a social group or a person on the basis of irrelevant characteristics such as ethnicity or gender.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Proficiency in a country's majority language correlates with migrant women's prenatal care utilisation (Eslier et al, 2023;Hamwi et al, 9900;Hamwi et al, 2022), self-perceived prenatal care communication quality (Hamwi et al, 2023), overall health (Dewalt et al, 2004). Higher levels of behavioural and socio-emotional problems among VP children growing up with language barriers are likely an indirect consequence of their mothers' and fathers' lived experiences in navigating the host society and its social systems.…”
Section: Discussionmentioning
confidence: 99%
“…Health communication and counselling for pregnant women are paramount to prevent poor pregnancy outcomes and ensure a positive pregnancy experience (12). Language barriers (13) and lack of good interpretation services (14), lower health literacy levels (15), and prejudicial attitudes and discrimination from healthcare providers (1) are potential barriers to equitable communication and care. A recent Norwegian study found that more than one-third of women with immigrant backgrounds did not understand the information provided during maternity care and 50% were unaware of whom to contact in case of pregnancy-related complications (16).…”
Section: Introductionmentioning
confidence: 99%